The Meaning of Home after Internal Migration for a Local-Based Community in Jakarta - Aris Masruri Harahap (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2023)
In the context of urbanization in Indonesia, home for migrants is often associated with a place where they will return after leaving. This idea becomes even clearer on Lebaran Day. At that time, many of those who left their homes will do their biggest effort to come home and meet their loved ones at home. It is not to mention people from Lampung who join a local-based community called Komunitas Anak Lampung Selatan (Community of People from South Lampung) or KALS. These people left their hometown for Jakarta in the spirit of accumulating economic capital. This essay discusses the meaning of home for migrants by using KALS as a study case in the context of urbanization in Indonesia. As the analysis shows, the home for KALS is not unified as it involves different places. Since KALS came to Jakarta to gamble their fate, the successful or unsuccessful effort in economic capital accumulation in Jakarta also plays an important role in the meaning construction of homes for KALS. Those who are satisfied with accumulating economic capital tend to see Jakarta as their current and future home. At the same time, they see Lampung as a home to which they will return on special occasions like Lebaran Day which means it is only temporary. However, those who are not satisfied with accumulating the capital tend to see Lampung as a home where they will return permanently in the future and see Jakarta as merely a temporary home.